Surface molecularly imprinted polymers with dummy templates for the separation of dencichine from Panax notoginseng1. Issue 60 (2nd July 2015) - Xie, Hongkai; Ji, Wenhua; Liu, Dahui; Liu, Wei; Wang, Daijie; Lv, Ruimin; Wang, Xiao
<x xml:space="preserve">Abstract</x> Surface molecularly imprinted polymers with dummy templates for the targeted separation of dencichine from Panax notoginseng.